A validated RP-UPLC method for estimation of Samidorphan and Olanzapine in mixed powder and combined tablets - Krishnaphanisri Ponnekanti; Ramreddy Godela (SpringerOpen, 2023)
Abstract Back ground The key objective of the research study is to develop a new stability-indicating RP-UPLC approach to determine the presence of Samidorphan and Olanzapine simultaneously in bulk and their combination. A successful separation of Samidorphan and Olanzapine was achieved by using HSS column C18 (100 × 2.1 mm), a mobile phase of 0.1% orthophospharic acid: Acetonitrile (70:30 v/v), flow rate of 0.3 mL/min, and detection wavelength of 230 nm. The stability of the analytes in bulk and dosage forms was evaluated using extreme forced conditions, such as hydrolysis with acid and base, peroxide oxidation, and heat degradation, following ICH guidelines. Results Olanzapine and Samidorphan had retention times of 0.46 and 0.93 min, respectively. Olanzapine and Samidorphan have linear responses from the proposed method in the concentration ranges of 5-30 µg/mL and 2.5-15 µg/mL, respectively. The computed detection and quantification limits for Olanzapine were 0.22 µg/mL and 0.471 µg/mL, and for Samidorphan were 0.12 µg/mL and 0.36 µg/mL. All method validation parameters have complied with the ICH guidelines' Q2 acceptance limits. The stability representing the feature of the approach has been seen with the excellent resolution among the Olanzapine and Samidorphan and degradation products. Conclusion The suggested RP-UPLC method was extremely sensitive, precise, and stable-indicating. The technique can potentially be used in the production of Olanzapine and Samidorphan for routine analysis in the quality control department. Graphical abstract